Visits at the primary clinic do not reduce ketoacidosis rates at presentation in type 1 diabetes mellitus. (14th September 2020) - Yona, Assaf; Haim, Alon; Friger, Michael; Chechik, Tzila Gartzia; Loewenthal, Neta; Hershkovitz, Eli
Abstract: Aim: The rate of diabetic ketoacidosis at time of diagnosis of type 1 diabetes remains high. We examined whether visits to a primary care clinic up to a month prior to diagnosis of new onset diabetes affected ketoacidosis rates. Methods: Retrospective chart review of children who were diagnosed with type 1 diabetes from January 1, 2010, to December 31, 2014. Data collection included demographics, age at diagnosis, number of visits to the primary care clinic during the month prior the diagnosis, relevance to diabetes and outcome of those visits and the presence of ketoacidosis at diagnosis. We examined the relationship between the rate of ketoacidosis at diagnosis and the number of visits in the clinic, and to the demographic characteristics. Results: Of 159 patients, 115 visited their clinic in the month prior to diagnosis of type 1 diabetes. The rate of ketoacidosis at diagnosis was similar between those who visited the clinic and those who did not (37.4% compared to 38.6%). There was no difference in ketoacidosis rates between the different ethnic and socio‐economic groups. Conclusion: Medical encounters in the month prior to diagnosis of type 1 diabetes did not reduce ketoacidosis rates in children.